Ethnic inequality and the crisis of governance: Comparative lessons from Nigeria and South Sudan - Asmorowati, Sulikah; Ceesay, Almamo (Faculty of Social and Political Science, Universitas Airlangga, 2025)
The postcolonial African state has frequently been conceptualised as an artificial construction. Ethnic inequality remains a critical yet underexplored structural determinant of governance failure in multi-ethnic states. This study explores how ethnic inequality contributes to governance crises in ethnically diverse states, focusing on Nigeria and South Sudan. This study was guided by the research question of whether ethnic inequality contributes to governance crises in Nigeria and South Sudan, and what lessons can be drawn for fragile states globally. It employs a qualitative comparative analysis to identify institutionalized and informal ethnic exclusion, revealing that Nigeria’s formal mechanisms for ethnic inclusion are undermined by elite capture and clientelism, leading to governance dysfunction. In contrast, South Sudan’s governance is dominated by informal ethnic militarism, resulting in state collapse. This study contributes new empirical and theoretical insights by linking ethnic inequality directly to the governance breakdown in fragile African states, offering lessons applicable to other divided societies.